2019
DOI: 10.1002/jcp.28395
|View full text |Cite
|
Sign up to set email alerts
|

VEGF‐A promotes angiogenesis after acute myocardial infarction through increasing ROS production and enhancing ER stress‐mediated autophagy

Abstract: Proangiogenesis is generally regarded as an effective approach for treating ischemic heart disease. Vascular endothelial growth factor (VEGF)‐A is a strong and essential proangiogenic factor. Reactive oxygen species (ROS), endoplasmic reticulum (ER) stress, and autophagy are implicated in the process of angiogenesis. This study is designed to clarify the regulatory mechanisms underlying VEGF‐A, ROS, ER stress, autophagy, and angiogenesis in acute myocardial infarction (AMI). A mouse model of AMI was successful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(92 citation statements)
references
References 57 publications
2
88
0
2
Order By: Relevance
“…Moderate ROS also upregulated Trx1 and Smyd1 in H9C2 cells, similar to what we found in intact hearts following exercise training. Despite excessive oxidative stress after MI being a contributing factor for cardiac remodeling [ 3 , 40 ], due to its action to increase cell permeability and trigger cell injury signaling pathways [ 41 ], ROS may also induce cardiac angiogenesis [ 58 ] and cardioprotection [ 59 , 60 ] in a dose-dependent manner. Indeed, here, we found that 50-200 µmol/L H 2 O 2 increased Trx1 expression and 300 µmol/L H 2 O 2 led to cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Moderate ROS also upregulated Trx1 and Smyd1 in H9C2 cells, similar to what we found in intact hearts following exercise training. Despite excessive oxidative stress after MI being a contributing factor for cardiac remodeling [ 3 , 40 ], due to its action to increase cell permeability and trigger cell injury signaling pathways [ 41 ], ROS may also induce cardiac angiogenesis [ 58 ] and cardioprotection [ 59 , 60 ] in a dose-dependent manner. Indeed, here, we found that 50-200 µmol/L H 2 O 2 increased Trx1 expression and 300 µmol/L H 2 O 2 led to cell death.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, appropriate amounts of ROS were shown to be proangiogenic factors through various mechanisms, including enhancing VEGF and angiopoietin‐1/Tie‐2 signaling (Harel et al, 2017; Zou et al, 2019). Besides, Nrf2 pathway played a direct or indirect positive role in regulating angiogenesis under oxidative stress.…”
Section: Nrf2 Pathway In Oxidative Stress‐induced Angiogenesismentioning
confidence: 99%
“…This process may be mediated by activated PI3K/AKT/ Hif-1α pathway [22]. Zou et al also demonstrated that upregulation of VEGF in the rat model of acute myocardial infarction stimulates ROS production, which in turn induces oxidative stress in the endoplasmic reticulum, as well as autophagy, thereby promoting cardiac neovascularization [23]. This study revealed that VEGF protein amounts were increased after treatment with YiQiFuMai.…”
Section: Discussionmentioning
confidence: 51%